Canned Fish: Creating HACCP Plan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
The fish canning industry is significant in the world food supply chain; it provides adequately packaged, shelf-stable fish protein products consumers need. This paper examines the canning process, the all-important aspects of food safety involved in canned fish processing, and the use of HACCP in the bid to guarantee safety and quality. The dangers of microbial contamination, histamine poisoning, and botulism are described and the precautions needed during the entire canning process. The paper also further discusses the global regulatory environment of fish canning industries in compliance with legal requirements on food safety in industries such as the FDA and EU regulations. Moreover, spoilage concerns under processing and post-process contamination have been highlighted, clearly showing how they affect the safety and quality of canned fish products. The paper also considers industry trends such as advancing technologies, consumer trends of going natural or produced with minimal processing as adopted by the Dole Food Company, and measures towards environmental sustainability. The increasing attention to environmental issues means that new advancements, such as efficient power consumption in processing and reusable packaging, are becoming critical. However, HACCP remains at the center of food safety assurance, bearing in mind that the food industry was changing, as stated above, during the development of HACCP. This paper further asserts that HACCP will remain the industry benchmark because of the reliability, flexibility, and cost efficiency of attaining high food safety standards in such a dynamic environment as new technologies and customers' tastes. In this paper, the author emphasizes that HACCP plays a significant part in the future evolution of canned fish and their quality characteristics.